ANALISIS SEGMENTASI PASAR PADA PD. BPR-NTB LOMBOK TIMUR CABANG LABUHAN LOMBOK BERDASARKAN GAYA HIDUP KONSUMEN - HERLINA, SILFIA (GANEC SWARA, 2018)
The purpose of this study is to know the Segmentation of Market Based on consumer lifestyle on Perusahaan Daerah Bank Perkreditan Rakyat – NTB, Lombok Timur, Labuhan Lombok branch.From the analysis of factors done it seems that from 39 items of questions 12 factors are formed, namely Activist, Oriented, Optimistic, Save and Clean, Hedonis, Apathy, Careful, Home, Information Finder, Confidence, Socialist, and Full of Hope. Then several factors are merged, so there are 5 segments of the consumer market on PD. BPR-NTB Lombok Timur Labuhan Lombok branch which serve as a reference to determine the target market, those segments are Indoor, Dynamic, Collective, Analytical, and Apathy which all formed after doing analysis calculation.Regarding to consumer profile of each segment in the market segment in this study, it is seen that the Indoor segment represents 25.38% of the respondents PD. BPR-NTB Lombok Timur Labuhan Lombok branch as a whole, Dynamic 12.50%, Collective 27.50%, Analytical 13.33% and Apathy which amounted to 20.83%.